Drømmen om Sydhavet: Biopolitik og seksualitet i Denis Diderots Supplément au voyage de Bougainville - Fastrup, Anne; Eliassen, Knut Ove (1700-tal: Nordic Journal for Eighteenth-Century Studies, 2010)
The Dream of the Pacific: Bio-Politics and Sexuality in Denis Diderot’s Supplément au voyage de BougainvilleAn important issue in the economic debates of the eighteenth century was the concern that the advanced Europeans nations were facing a decline in population. It was assumed that this would have considerable consequences for the economic and military strength of countries like France and England. The idea that the decline was an effect of the European countries’ advanced state of civilisation was widespread; accordingly, explorers like James Cook and Louis Antoine de Bougainville were eager to examine the ways in which the societies and cultures they encountered organised sexual reproduction. Informed by the travelers’ accounts, and recognising the possible insights these offered for the challenges France was facing, Denis Diderot’s Supplément au voyage de Bougainville analyses and discusses the sexual mores of the inhabitants of Tahiti. Taking as its starting point the oblique and slightly idiosyncratic way in which the French philosopher addresses the issue — in the form of an apocryphal “supplement” to Bougainville’s account supposedly written by the explorer himself — this essay analyses the way in which Diderot transforms an ethnographic reflection on Polynesian culture into an analysis of the pathologies of his contemporary France from the double perspective of economy and ethics.
Keywords: Tahiti; Diderot; Bougainville; Bio-Politics; Population; Supplement